Isolation and Culture of Primary Human Dental Pulp Cells—A Description of Technical and Methodological Steps to Maximise Predictability and Yield - Michaela Kearney; David E. McReynolds; Henry F. Duncan (Methods and Protocols, 2024)
The dental pulp has critical functions in tooth development as well as an ongoing role in promoting and maintaining the vitality of teeth. In particular, its regenerative ability allows dental tissues to be restored following damage caused by traumatic injury or caries. Regenerative endodontic procedures aim to utilise these processes to stimulate dental pulp repair in a minimally invasive manner and reduce the need for more invasive procedures such as root canal treatment. Dental pulp is a source of dental pulp cells (DPCs), which has a subpopulation of dental pulp stem cells (DPSCs), which are attractive for use in regenerative medicine due to their high proliferation rate, ability to differentiate into multiple cell types, and their preserved vitality following cryopreservation. The development of next-generation clinical therapeutics that maximise the potential of dental pulp relies on strong empirical evidence arising from in vitro experimentation. Here, we describe a modified method for the efficient isolation of primary human DPCs from sound third molar teeth for culture using an explant outgrowth method on basement membrane-coated flasks, as well as using high-resolution macro-photography to illustrate the methods. Critically, steps are taken to minimise potential physical and mechanical trauma to the cells and maximise yield. Human DPCs cultured using this method can be further expanded in cell culture flasks to facilitate their use in various in vitro experimental procedures.